IS OUR CHILD TOO YOUNG TO LEARN ABOUT GENDER EQUALITY? AN INTERPRETATION OF GENDER EDUCATION IN ACEH FAMILIES - Kiram, Muhammad Zawil (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
This study aims to reveal gender-based discrimination, forms of gender education, and the importance of gender education in Acehnese families. This study was conducted by using the method of descriptive qualitative with data collection techniques through observation and interview. The result showed that in Acehnese families, the forms of gender-based discrimination that often faced by women are inequality in housework distribution and childcare. In Aceh, most men still play fewer roles in taking care of children because domestic jobs are seen to be women’s’ responsibilities. Another form of gender-based discrimination in Aceh is domestic violence against women. The result also demonstrated that in Acehnese families there is no gender education because many people do not understand the term of gender equality and gender issues are considered as western culture and still taboo to discuss. Gender education in the family is important because children acquire gender stereotypes at an early age, and they learn about gender equality from their family for the first time. Teaching gender equality to children is never too early, and they never too young to learn about it, they would come out and bring the gender equality in the family and society in general as they will be the pioneer or gender equality when they reach adulthood.